Estrategias de cobranzas para la recuperación de cartera en la Jefatura de Cartera y Agencias de la Empresa Eléctrica Provincial Cotopaxi S.A. - Catota Oleas, Virginia Elizabeth (2022)
Portfolio recovery is important because it allows to eliminate the risk of corporate bankruptcy due to lack of timely collection of credits granted. The main objective of this research was to design collection strategies that contribute to the recovery of overdue portfolio in the Portfolio Headquarters and Agencies of the Electric Company of the Province of Cotopaxi, an inductive-deductive approach was used to know the object of study, analytical synthetic to identify the problem of study and the logical historical method to determine the trajectory of events and their operation, the field research was carried out through observation, interview and survey, while the bibliographical research through documentary review. It was found that during the COVID 19 pandemic, despite the fact that more than 50% of clients had delays in electricity bill payments, 87% of them did not receive any reminder for pending payments; the main reason for not having made their payments on time was due to lack of employment.